BANGUNAN TEOLOGI DAKWAH ISLAM - Salmadanis Salmadanis (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2018)
Theology is the ability to give meaning to worship for every behavior and activity, and with the principle of "only because of God". People who have theological intelligence always have more energy. Changes in society, not only determined by academics, but together with theology (belief) that surrounds it. The Prophet Muhammad in carrying out his leadership as a missionary leader, did not escape from his beliefs. This belief is reflected in every activity and behavior within a radius. The study of Islamic da'wah theology with topics that occur in long distances, produces very important meanings from various parties whose Islamic theological material is less successful in its mission to complete duras.